Updates in Liver Cancer - Mohamed Abdeldayem, Hesham (IntechOpen, 2017)
Liver cancers result in considerable amount of financial and social burden. On the other hand, researches and clinical studies related to liver cancers continue to advance at a rapid pace. The chapters in this book provide state-of-the-art reviews on the current knowledge and advances in research and management of liver cancers. It includes the most recent advances in that field, particularly, hepatocarcinogenesis and the potential role of intestinal microbiota, nonalcoholic steatohepatitis, cancer stem cells, aldehyde dehydrogenase-1, and hepatitis B virus. This book also discusses the methods of diagnosis of HCC, the minimally invasive therapies for liver cancers, living donor liver transplantation for HCC, surgical management of liver metastases from colorectal cancers, and assessment and optimization for the future liver remnant.